2022
DOI: 10.3389/fmicb.2022.938153
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lactic Acid Bacteria Additives on the Quality, Volatile Chemicals and Microbial Community of Leymus chinensis Silage During Aerobic Exposure

Abstract: Silage exposed to air is prone to deterioration and production of unpleasant volatile chemicals that can seriously affect livestock intake and health. The aim of this study was to investigate the effects of Lactobacillus plantarum (LP), Lactobacillus buchneri (LB), and a combination of LP and LB (PB) on the quality, microbial community and volatile chemicals of Leymus chinensis silage at 0, 4, and 8 days after aerobic exposure. During aerobic exposure, LP had higher WSC and LA contents but had the least aerobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 77 publications
5
11
0
Order By: Relevance
“…The increase of acetic acid content in the LB group was closely related to the slow conversion of lactic acid into acetic acid by LB. The research results of Ranjit et al [22], Nishino et al [23] and Liu et al [24] are consistent with this experiment, i.e., the addition of LB to silage can increase the acetic acid content and effectively improve the aerobic stability of silage. Muck et al [9] noted that in about a third of studies, homofermentative inoculants reduced aerobic stability and that this situation occurred more often in corn silage than in grass or legume silage.…”
Section: Effects Of Lab On the Fermentation Quality And Aerobic Stabi...supporting
confidence: 83%
“…The increase of acetic acid content in the LB group was closely related to the slow conversion of lactic acid into acetic acid by LB. The research results of Ranjit et al [22], Nishino et al [23] and Liu et al [24] are consistent with this experiment, i.e., the addition of LB to silage can increase the acetic acid content and effectively improve the aerobic stability of silage. Muck et al [9] noted that in about a third of studies, homofermentative inoculants reduced aerobic stability and that this situation occurred more often in corn silage than in grass or legume silage.…”
Section: Effects Of Lab On the Fermentation Quality And Aerobic Stabi...supporting
confidence: 83%
“…During aerobic exposure, the abundance of thick-walled bacterial phyla increased slightly in the initial stage in each treatment group and decreased significantly in the later stages in the CK and LP groups. This was due to the poor inhibition of aerobic microorganisms in the CK and LP groups, leading to a rapid increase in other phyla, which is consistent with the results of Liu et al [ 49 ].…”
Section: Discussionsupporting
confidence: 91%
“…Similar effects were found by Xiong et al [ 48 ] after the addition of Lactobacillus propionic and Lactobacillus paracasei to oat silage, which may be due to the fact that the pasture itself began to proliferate with attached lactobacilli after the inhibition and disappearance of miscellaneous bacteria in the first stage of silage fermentation, and the addition of exogenous lactobacilli stimulated the competition of attached lactobacilli, resulting in higher OTU and Chao1 values of the lactobacilli added group than CK in the later stage of silage. After aerobic exposure, the OTU and Chao1 values in the LP group were higher than the other groups, indicating that LP could not effectively inhibit the growth of various bacteria in the aerobic exposure stage, while the lactic acid produced during aerobic exposure could provide substrate for the growth and reproduction of harmful bacteria, as was also shown in the study by Liu et al [ 49 ]…”
Section: Discussionmentioning
confidence: 63%
“…The composition and distribution of fugal are the key players in aerobic stability. During the aerobic exposure stage, the growth of undesirable microorganisms could lead to the deterioration of nutrients in silage and modify the aerobic stability [16]. Weinberg et al [17] showed that the presence of fungi in raw materials and silages could directly influence the accumulation of mycotoxins and aerobic stability.…”
Section: Introductionmentioning
confidence: 99%